Pengaruh Burnout Dan Ketidakamanan Kerja Terhadap Kepuasan Kerja Dalam Meningkatkan Kinerja Pada Tenaga Pendidik SMAN 1 Karangnunggal Di Tasikmalaya. - Elfa Indrian (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2020)
This study aims to determine how the effect of burnout and job insecurity on job satisfaction in improving the performance of the teaching staff of SMAN 1 Karangnunggal either partially or simultaneously. The research method used is descriptive and verification with a sample size of 58 respondents. Data collection techniques used were observation, interviews, and distributing questionnaires. The data analysis method used is path analysis (path analysis) and analysis of the coefficient of determination. The results showed that burnout and job insecurity at SMAN 1 Karangnunggal can be said to be quite good. Then job satisfaction and performance can be said to be good. Burnout and job insecurity have an effect on job satisfaction, which is 62.9%. Job satisfaction has an effect on performance, namely 67%, the dominant influence of the independent variable is burnout by 57%, while job insecurity is 28.7%.